2013
DOI: 10.5251/abjna.2013.4.3.275.279
|View full text |Cite
|
Sign up to set email alerts
|

Some physical properties and thin layer drying characteristics of local varieties of tomatoes (Lycopersicon lycopersicum)

Abstract: Tomato fruit is a perishable farm produce with high moisture content. Despite its valuable qualities, the fruits are subjected to wastage and spoilage during its seasonal period. The study was therefore conducted to investigate some physical properties of local variety of tomatoes that are relevant in the handling and processing of the fruits. The physical characteristics considered were axial dimensions, weight, volume, density, surface area and sphericity. The mean dimensions of the fresh fruits specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
0
4
1
Order By: Relevance
“…All varieties used contain a considerable amount of fiber in varying quantities. Onifade et al (2013) revealed that the percentage crude fiber in Yoruba variety of tomato was 2.50%, comparatively higher than not only the similar variety in the present study but also other three varieties considered in this current study. The principal components of dietary fibers are lignin, cellulose, hemicelluloses, pectins, resistant starch and non-digestible oligosaccharides.…”
Section: Discussioncontrasting
confidence: 45%
“…All varieties used contain a considerable amount of fiber in varying quantities. Onifade et al (2013) revealed that the percentage crude fiber in Yoruba variety of tomato was 2.50%, comparatively higher than not only the similar variety in the present study but also other three varieties considered in this current study. The principal components of dietary fibers are lignin, cellulose, hemicelluloses, pectins, resistant starch and non-digestible oligosaccharides.…”
Section: Discussioncontrasting
confidence: 45%
“…The ash content of the tomatoes was lower than the report by Garuba et at [14]. Ash is the inorganic residue that remains after incineration or complete oxidation of organic component of food and a representation of the total mineral content in food While dietary fibre is an important in [20]. The high ash content of the samples is an indication of good source of minerals.…”
Section: A Proximate Composition Of Fruits and Vegetables From Open Market And Shopping Mall In Port Harcourt Citymentioning
confidence: 63%
“…The bulk of tomato contained moisture. This explained why the crop had low shelf life (Onifade et al, 2013). The low fat content of the two varieties make tomato a good diet for heart diseases.…”
Section: Fruit Quality and Proximate Compositionmentioning
confidence: 99%